EFFICACY OF 50% INSULIN LISPRO AND 50% INSULIN LISPRO PROTAMINE SUSPENSION (HUMALOG MIX 50) VERSUS BIPHASIC INSULIN ASPART (NOVOMIX 30) IN PATIENTS WITH TYPE 2 DIABETES MELLITUS DURING RAMADAN - EW, Nur Aini; Zamrud AA, Rosdina; MS, Fatimah Zaherah; Z, Nur Aisyah; WMH, Sharifah Faradila; A, Mohd Hazriq; AG, Rohana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The month of Ramadan has always been challenging to patients and doctors due to the increased risk of hypo- and hyperglycaemia attributed to large meals during the breaking of fast. Previous studies demonstrated that both Humalog Mix 50 and NovoMix 30 are safe in Ramadan. However, there is little information on their efficacy and safety in Asian populations. The aim of this study is to evaluate the efficacy and safety of Humalog Mix 50 in comparison to NovoMix 30 in patients with type 2 diabetes mellitus (T2DM) during Ramadan. METHODOLOGY We performed a prospective study in T2DM patients seen at the Endocrinology Clinic of UITM in the year 2018, who fasted during Ramadan. They were randomized to receive either Humalog Mix 50 or NovoMix 30. Weight and fructosamine pre- and post-Ramadan, capillary glucose at 4-points per day (pre-sahur, noon, pre-iftar and post-iftar) were recorded. RESULTS Twenty-three (23) patients (15 on NovoMix 30 and 8 on Humalog Mix 50) with an overall mean age of 57 were analysed. NovoMix 30 showed a better glycaemic trend at pre-sahur (8.3 ± 1.8 vs 9.3 ± 1.4), during the day (7.4 ± 0.9 vs 7.7 ± 1.5), and 2-hours post-iftar (10.1 ± 2.7 vs 10.4 ± 3.8), although not significant. There were 4 patients who experienced hypoglycaemia in the NovoMix 30 arm (one with glucose 3.3 mmol/L (noon during fasting), and the others with glucose 3.8 mmol/L. Fructosamine difference pre- and post-Ramadan showed reduction of 12.62 mmol/L (HbA1c 1.82%) with Humalog Mix 50 and 7.133 mmol/L (HbA1c 1.73%) with NovoMix 30 (p=0.69). Weight and waist circumference differences pre- and post-Ramadan were not significant; there was more weight reduction (-1.48 vs -0.53 kg) and waist circumference reduction (-1.07 vs +1.50 cm) with NovoMix 30. CONCLUSION Humalog Mix 50 demonstrated similar efficacy and safety compared to NovoMix 30 during Ramadan in T2DM with a potential benefit on fructosamine reduction.